2019
DOI: 10.1111/ijpo.12517
|View full text |Cite
|
Sign up to set email alerts
|

The potential for long‐term cost‐effectiveness of obesity prevention interventions in the early years of life

Abstract: Summary Background Early childhood obesity prevention is gaining increasing importance, as the prevalence of children with overweight and obesity aged 5 years and under increases worldwide. Along with understanding the effectiveness of obesity interventions, it is important to understand the cost‐effectiveness of interventions over time. Objectives To estimate the long‐term health benefits and health care cost‐savings of reductions in BMI for the Australian population of children aged between 2 and 5 years. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 47 publications
0
67
0
Order By: Relevance
“…A number of studies reported marginal effects that were not statistically significant (Ostbye et al, 2012;Paul et al, 2011;Woo Baidal et al, 2017); however, most studies did not have longterm follow-up of the interventions. Also, the nature of the age group, under-fives, means that dietary habits formed at this age are likely to lifelong influence in relation to food preferences, making interventions at this stage of life very cost-effective (Brown et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies reported marginal effects that were not statistically significant (Ostbye et al, 2012;Paul et al, 2011;Woo Baidal et al, 2017); however, most studies did not have longterm follow-up of the interventions. Also, the nature of the age group, under-fives, means that dietary habits formed at this age are likely to lifelong influence in relation to food preferences, making interventions at this stage of life very cost-effective (Brown et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, early childhood obesity prevention is required because the prevalence of overweightness and obesity in children aged 5 years and below has been increasing worldwide [33]. In Japan, examinations of physical and mental development were performed on young children at 1.5 and 3 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to needing accurate techniques to assess adiposity levels, it is also important to understand the precision of a technique. Estimates show that a −0.13 reduction in the BMI z‐score of 2 to 5 year olds that is maintained, equates to significant health care cost savings ($301 million) over a lifetime . Therefore, as obesity prevention interventions are considered, it is imperative to have sensitive techniques to detect small changes in adiposity to better evaluate intervention efficacy.…”
Section: Introductionmentioning
confidence: 99%